An anchored retaining wall in CSM - Correia, A. Gomes (2013)
Cutter soil mixing (CSM) is being recently used in Portugal in several applications. This paper describes a solution in cutter soil mixing reinforced with vertical steel profiles IPE270 for a retaining wall with 66 m long and 13 m high constructed in geological formations of landfill materials, Miocene sandy soils and sandstones, with a phreatic level around 8 m depth. This construction is done nearby commercial buildings. The solution is justified against more classical solutions for anchored retaining walls considering the following aspects: feasibility of CSM in the geological and environment conditions, predict behaviour during and post construction, simplicity of construction process, time of construction, economy and quality assurance. Numerical modelling using a commercial program is carried out, based in geotechnical parameters established at the project level, showing a good agreement of the observed data, in terms of horizontal displacements of the wall and also of the safety levels against bending, shear and compression.